The Puffin Book of Stories for Five - Years - Olds - Cooling, wendy; Cox, Steve (London Puffin Books, 1996)
Suitable for every five-year-olds to share or read aloud, this title includes seventeen stories, full of adventure and magic, by much-loved writers, including Margaret Mahy, Ted Hughes and Malorie Blackman
English Stories
1 2 14
Keywords: English stories